Determination Permeability Coefficient from Piezocone. (26th April 2014) - Wang, Qiang; Tong, LiYuan
Abstract : The permeability coefficient of soil profile is one of the problems concerned by engineers, and the determination of permeability coefficient method mainly relies on the laboratory permeability test and field pumping test, but these tests are time-consuming and inefficient, and especially the permeability coefficient of soil under the condition of partial drainage was difficult to determine; in this paper, the modern digital CPTU technology was used. Dimensional permeability K T was defined by using the dimensionless normalized cone tip resistance Q t, friction factor F r, and pore pressure ratio B q, these parameters enable plots of B q -Q t, F r -Q t, B q -F r to be contoured K T and hence for permeability coefficient. The relationship has been applied to Nanjing 4th Yangtze river bridge, and compared with laboratory penetration test. The results indicate that the method can accurately determine the permeability coefficient of soil under partial drainage condition and provide the theoretical basis for engineering application.